Blow-ups and Fano manifolds of large pseudoindex - Novelli, Carla (MATHEMATICA SCANDINAVICA, 2019)
We describe the Kleiman-Mori cones of Fano manifolds of large pseudoindex that admit a structure of smooth blow-up.